Facial emotion recognition accuracy in women with symptoms of polycystic ovary syndrome: Reduced fear and disgust perception - Shree Smruthi Venkateshan; Kirsten A. Oinonen (Women's Health, 2025)
Background: Research suggests that women with polycystic ovary syndrome (PCOS) are more likely to suffer from mental health disorders, emotional distress, and have altered hormone profiles (e.g., higher androgens). Past research suggests facial emotion processing is affected by hormones (e.g., androgens), mental health-related disorders, and may be altered in PCOS. Objectives: The present study examined whether facial emotion recognition (FER) differs between women with and without PCOS symptoms. Design: Observational case-control design. Methods: Three groups of participants (women with provisional PCOS, women without PCOS, and men; N  = 178) completed a FER task that involved identifying emotions (anger, disgust, fear, happiness, sadness, surprise, or neutral) in images of emotional faces. Overall emotion recognition and emotion-specific accuracy were examined. PCOS symptom severity and provisional diagnoses were also assessed in women via self-report measures, including the polycystic ovary syndrome questionnaire. Results: Women with provisional PCOS had significantly lower emotion recognition accuracy than those without PCOS, and emotion-specific differences were found for fear and disgust. A significant linear effect also emerged for overall FER, revealing men as the least accurate, followed by women with provisional PCOS, and then women without PCOS. Conclusions: The results suggest that women with PCOS may have difficulty with emotion recognition, especially fear and disgust. The sex difference in emotion recognition was in line with previous research. These findings are consistent with the theory that androgens affect emotion recognition and suggest implications for PCOS symptoms on women’s emotional well-being and socioemotional functioning.